Validation of Padjadjaran Memory Rehearsal Application (PMRA) as A Tool for Measuring Working Memory Using Digit Span and Knox Cube - Ira Terahadi; Lenny Kendhawati; Afra Hafny Noer (Universitas Katolik Soegijapranata, 2020)
This study intends to test the validity of PMRA based on relationships with other variables and internal structures. This non-experimental quantitative approach in 61 children aged 5-8 discusses the correlation between PMRA with digit span and knox cube. Pearson product moment indicates that PMRA has a positive significant correlation with digit span and knox cube; i.e. PMRA verbal deret maju with digit forward (r=.557, p=